Social determinants of congenital syphilis health in an insurance company in Valle del Cauca 2015-2020 - Giraldo-Oliveros, Simón Andres (2024)
Objective: To establish the structural and intermediate determinants that best explain the outcome of congenital syphilis. Material and Methods: Descriptive observational study with analytical intention and focus on social determinants of health, carried out in a cohort of pregnant women confirmed with gestational syphilis, active members of an insured person in Valle del Cauca between 2015 and 2020, exploratory analysis was carried out by absolute frequencies. and related bivariate analyzes with contingency tables using the chi square test and multivariate logistic regression analysis. Results: A higher volume of cases of gestational syphilis was found in women living in urban areas, in the subsidized regime, in socioeconomic status one or two, and in vulnerable population groups such as displaced persons, in prison, and residents of the municipalities of Cali and the district of Bonaventure. Conclusions: The structural and intermediate determinants that increase the probability of congenital syphilis outcome were pregnant women in the subsidized regime, rural area, indigenous and ROM (gypsy) ethnic groups, socioeconomic stratum 2, with late diagnosis, absent prenatal check-ups, without screening tests, without their own treatment or contacts, residents in municipalities far from the capital and with a higher infant mortality rate.